PENGARUH PENGGUNAAN METODE PEMBELAJARAN RESITASI TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK BUNYI DI SMA NEGERI PADANGSIDIMPUAN - Sari, Lia Purnama (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2022)
The aim of this research was to know whether there was a significant influence between resitasi method on student’s achievement in sound subject at twelfth grade student’s of SMA Negeri 6 Padangsidimpuan before and after using resitasi method. The method used is the method of experimental that is to look for the influence certain variable to other variables. The population of this research was all the twelfth grade students of SMA Negeri 6 Padangsidimpuan which include 3 classes or 92 students. By applying stratified sampling techbique, the writer took 92 students as the sample. Instruments used as a data collection tool is observation and tests. Then the research data is processed in two stages where the first stage to the second stage of analysis with descriptive and inferential analysis. Based on the result of this research, resitasi method had the average 91. It was categorized “very good”. While the students achievement in sound subject before given pretest at twelfth grade student’s of SMA Negeri 6 Padangsidimpuan had the average 68. It was categorized “enough”. While posttest on students achievement in sound subject before at twelfth grade student’s of SMA Negeri 6 Padangsidimpuan had the average 82. It was categorized “good”. Result of this research had gotten by using t-test formula had gotten tcount 6.46. If compare by ttable in confident level significant df = N – 2 = 92-2=90. it could be gotten that ttable = 0,228. It could be gotten that ttable= 1.665 It could be seen that tcount was greater ttable (6.46>1,665). The alternative hypothesis was accepted. It maens that there was a significant influence between resitasi method on student’s achievement in sound subject at twelfth grade student’s of SMA Negeri 6 Padangsidimpuan.